THE IMPORTANCE OF THE ROLE OF PARENTS IN REGARDING NEEDS BALANCED NUTRITION FOR EARLY CHILDREN - Hidayani, Wulan Aulia; Ismaniar, Ismaniar; Putri, Lili Dasa (IKIP Siliwangi Bandung, 2025)
The purpose of making this journal is to analyze the important role of parents in meeting the nutritional needs of early childhood. The technique used is a literature review where this research focuses on how to increase people's knowledge of the needs of early childhood. By participating in this research, there is several kinds of information through journals, articles, guidebooks, newspapers and mag azines that discuss the importance of the role of parents in the needs of early childhood.